Country, sex, and parent occupational status: Moderators of the continuity of aggression from childhood to adulthood. Issue 6 (2nd July 2014) - Kokko, Katja; Simonton, Sharon; Dubow, Eric; Lansford, Jennifer E.; Olson, Sheryl L.; Huesmann, L. Rowell; Boxer, Paul; Pulkkinen, Lea; Bates, John E.; Dodge, Kenneth A.; Pettit, Gregory S.
<x xml:space="preserve">Abstract</x> Using data from two American and one Finnish long‐term longitudinal studies, we examined continuity of general aggression from age 8 to physical aggression in early adulthood (age 21–30) and whether continuity of aggression differed by country, sex, and parent occupational status. In all samples, childhood aggression was assessed via peer nominations and early adulthood aggression via self‐reports. Multi‐group structural equation models revealed significant continuity in aggression in the American samples but not in the Finnish sample. These relations did not differ by sex but did differ by parent occupational status: whereas there was no significant continuity among American children from professional family‐of‐origin backgrounds, there was significant continuity among American children from non‐professional backgrounds. Aggr. Behav. 40:552–567, 2014. © 2014 Wiley Periodicals, Inc.